A Quasi Experimental Study of Helicobacter Pylori Eradication in Afghanistan: Comparison of Treatment Preferences for Helicobacter Pylori Eradications, Sequential Therapy Versus Hybrid Therapy - Jan, Rauf; Alam, Sher; Najeebullah; Zadran, Mohammad Ashraf (Journal for Research in Applied Sciences and Biotechnology, 2023)
Colonization by Helicobacter pylori (H. pylori) of the gastric epithelial lining epitomizes a pervasive and clinically consequential infectious etiology. Therapeutic strategies aimed at bacterial eradication inherently hinge on a confluence of determinants-regional antimicrobial resistance spectra, localized clinical algorithms, and pharmaceutical attainability. Best practices in the medical milieu underscore sagacious antibiotic stewardship, predicated on a patient-centric antibiotic historiography prior to therapeutic commencement. The overarching objective of this study-executed in a quasi-experimental comparative framework at Sheikh Zayed University Teaching Hospital, Khost, Afghanistan-was to discerningly evaluate and contrast two paradigms of treatment: Sequential Therapy and Hybrid Therapy. The subject pool encapsulated a demographically diverse set of individuals, aged 16 to 80, manifesting symptoms of peptic ulcer diseases or gastritis. Those ineligible for inclusion included follow-up patients, immunocompromised subjects, and individuals undergoing oncological interventions. Employing the Statistical Package for the Social Sciences (SPSS) Version 25 for data stratification, the Hybrid Therapy arm was subjected to an initial seven-day treatment window with amoxicillin (1g, BID) and omeprazole (20mg, BID), succeeded by a seven-day regimen involving clarithromycin (500mg, BID) and metronidazole (400mg, TID). Conversely, the Sequential Therapy cohort received a bifurcated, five-day course of omeprazole and amoxicillin, followed by an additional five-day regimen of omeprazole, metronidazole, and clarithromycin. Outcome variables, inclusive of treatment efficaciousness, regimen completion, and patient adherence, were rigorously evaluated via Chi-Square statistical testing. Encompassing 145 patients, the study observed a gender dispersion of 156 males (41.1%) to 224 females (58.9%). Per-protocol analysis unveiled a statistically significant eradication rate-86.8% vs 83.0% (P=0.021)-tilted in favor of Hybrid Therapy. Both Modified Intention-to-Treat and Intention-to-Treat analyses corroborated this proclivity, registering significant eradication rates of 92.1% versus 67% (P=0.031) for Hybrid Therapy. Conclusively, Hybrid Therapy demonstrated a superior safety and efficacy profile vis-à-vis Sequential Therapy in extirpating H. pylori, intimating its plausible preferability for the clinical management of associated peptic ulcer diseases and gastritis.